Modelling the noise generated by railway transport: statistical analysis of modelling results applying CADNAA and IMMIprograms - Paožalytė, Ilona; Grubliauskas, Raimondas; Vaitiekūnas, Petras (Journal of Environmental Engineering and Landscape Management, 2012)
To avoid a negative impact on human health, Lithuania, alike other countries, pays full attention to reducing noise in the environment. One of the implemented actions against noise sources and the way to reduce it is a composition of strategic maps. Research focuses on the performance of modelling noise dispersion employing CadnaA and IMMI software and proposes the analysis of the actuarial reliability of the above-mentioned programs. The dispersion of the noise generated by railway transport has been modelled in the dwelling area of Klaipeda railway station. The chosen zone covers a sector of 500 m in length and is situated at the distance of 150–200 m from this sector. Modelling noise dispersion maps applying both programs displayed that the maximum level of noise caused by day and night railway transport was registered near railway during both periods of time and varied from 75 to 80 dBA, whereas at the locations of 150–200 m that are more distant from the railway line, the level of noise gradually reduces and reaches the level of 35–50 dBA in cases CadnaA or IMMI programs are introduced. Program STATISTICA along with Mann Whitney U and Kolmogorov–Smirnov D non-parametric statistical tests were used for assessing the actuarial reliability of modelling programs used for noise dispersion. The obtained data indicate that the level of significance p was not exceeding the value of 0.05 in all cases. Article in English. Geležinkelio transporto keliamo triukšmo modeliavimas ir statistinė rezultatų analizė Santrauka. Lietuvoje, kaip ir kitose šalyse, daug dėmesio skiriama triukšmui aplinkoje mažinti siekiant išvengti jo neigiamo poveikio sveikatai, aplinkos kokybei. Viena iš triukšmo ir jo poveikio mažinimo priemonių yra strateginių žemėlapių sudarymas. Tyrimo tikslas – atlikti triukšmo sklaidos modeliavimą programomis CadnaAir IMMI bei pateikti šių programų statistinio patikimumo analizę. Modeliuojama geležinkelio transporto triukšmo sklaida Klaipėdos geležinkelio stoties gyvenamojoje teritorijoje 500 m ilgio geležinkelio ruože ir per 150–200 m nuo jo. Modeliuojant geležinkelio transporto dieną ir naktį sukeliamo triukšmo sklaidą nustatyta, jog abiem nagrinėtais laikotarpiais abiejų programų pateiktuose triukšmo sklaidos žemėlapiuose didžiausias triukšmo lygis – nuo 75 iki 80 dBA fiksuojamas šalia geležinkelio bėgių. Tolstant nuo bėgių, triukšmo lygis tolygiai mažėja, 150–200 m atstumu siekia 35–50 dBA ir CadnaA, ir IMMI triukšmo sklaidos modeliuose – ir dieną, ir naktį. Triukšmo sklaidos modeliavimo programų patikimumas vertintas programa STATISTICA bei Mann Whitney U ir Kolmogorov–Smirnov D neparametrinės statistikos testais. Šie rodė, jog reikšmingumo lygmuo p visais atvejais neviršijo 0,05 reikšmės. Todėl teigiama, kad abiejų modeliavimo programų pateikti rezultatai patikimi. Reikšminiai žodžiai: geležinkelio triukšmas, triukšmo lygis, CadnaA , IMMI